Tinjauan Hukum Islam Terhadap Praktik Arisan Daging Di Desa Slempit Kecamatan Kedamean Kabupaten Gresik - Dani El Qori; Habib Masyhudi (MASADIR: Jurnal Hukum Islam, 2022)
Arisan is one of the contemporary muamalah practices that is very much in demand today. Among the types of social gathering that developed in society is the gathering of meat. The social gathering of meat is carried out by the community in Slempit Village, Kedamean District, Gresik Regency. As the name suggests, the social gathering of meat is done with a payment that is in accordance with the unit price of meat on the market. Meanwhile, it can be seen that the price of meat in the market sometimes increases or decreases. This study analyzes how the implementation of social gathering meat in Slempit Village, Kedamean District, Gresik Regency and how Islamic law reviews the practice of social gathering meat in Slempit Village, Kedamean District, Gresik Regency. The approach used in this study is a qualitative descriptive approach. The results of this study indicate that the meat gathering in Slempit Village, Kedamean District, Gresik Regency is carried out by every member of the meat gathering who will carry out celebrations such as walimatul 'ursy, circumcision and birthdays. The nominal gathering of meat is in accordance with the unit price of meat on the market. The practice of gathering meat in the village of Slempit is identical to the qard contract. This practice is not valid according to the Shafi`I school because it does not use sighat ijab qabul. This practice is also illegal according to the majority of scholars because there is a difference in fees when there is an increase in the price of meat.